2020
DOI: 10.1021/acs.jpcb.0c07173
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Liesegang Structures under the Conditions of the Spatiotemporal Reaction of Polymer-Analogous Transformation (Salt → Base) of Chitosan

Abstract: This paper presents the results of our study of the diffusion front progression of OH − ions in the bulk of a flat layer of the salt chitosan form during the course of the chemical reaction of the polymer-analogous salt → base transformation, accompanied by the formation of a water-insoluble polymeric phase as a gel film with its structure of concentric rings or tangential bands. Using scanning electron microscopy and polarization microscopy, structural and morphological features of these periodic formations w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…13 Although there were a few studies that focused on the spatiotemporal analysis of pattern formation, they overlooked the formation process of the single band, which is the basic unit of the pattern. 8,11,18 (3) Pattern formation has been considered a result of simple precipitation, 6,10,11,18 which omits the complicated process where constituent precipitates are actually developed by the aggregation of primary particles larger than atoms/ions/ T h i s c o n t e n t i s molecules. Recently, an increasing number of discoveries have indicated that crystallization proceeds through the attachment of amorphous intermediate precursors.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…13 Although there were a few studies that focused on the spatiotemporal analysis of pattern formation, they overlooked the formation process of the single band, which is the basic unit of the pattern. 8,11,18 (3) Pattern formation has been considered a result of simple precipitation, 6,10,11,18 which omits the complicated process where constituent precipitates are actually developed by the aggregation of primary particles larger than atoms/ions/ T h i s c o n t e n t i s molecules. Recently, an increasing number of discoveries have indicated that crystallization proceeds through the attachment of amorphous intermediate precursors.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Theories including prenucleation and postnucleation theories were proposed to explain band formation based on the interaction between the reaction and diffusion, , and numerical simulations were attempted to exquisitely interpret the pattern formation. Recently, attention has been turned to controlling the spacing and width of the bands because of a resurgent interest in their applications in materials science as a bottom-up fabrication tool, , as well as in the fundamental studies of biogenic patterns. , …”
Section: Introductionmentioning
confidence: 99%
“…They can be designed by a bottom-up approach starting from initial building blocks and creating the structure on a smaller length scale. , Building an ordered polysaccharide polymer structure always gains attention as it enhances the functionality and performance of soft materials. , The natural polysaccharide polymer chitosan (CS) is a potential candidate because of its biomedical applications , and intrinsic properties such as biocompatibility, biodegradability, and bioactivity . The sol–gel transition leads to a multilayered CS polymer using special molds, stopping the gelation process , or starting from appropriate salt compound …”
Section: Introductionmentioning
confidence: 99%
“…12 The sol−gel transition leads to a multilayered CS polymer using special molds, 13 stopping the gelation process 14,15 or starting from appropriate salt compound. 16 Monitoring the material ion composition, properties, and interaction strength helps in designing complex patterns of soft structures, which are utilized in a wide range of applications including stretchable electronics, 17 biotemplating, 18 biomineralization, 19 bioactuation, 20 3-D printing, 21 and so forth. In the last few years, CS interaction with metal ions has earned significant attention 22 in waste water cleaning.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Chitosan is composed of arbitrarily distributed β-(1-4)-linked d -glucosamine (deacetylated unit) and N-acetyl- d -glucosamine (acetylated unit), which exhibits impressive characteristics, including mucoadhesive, biodegradable, and biocompatible properties. Chitosan has emerged as an essential element in the development of a nano-particulate delivery vehicle ( Abolhasani et al, 2020 ; Babicheva et al, 2020 ; Palomino-Durand et al, 2020 ; Majcher et al, 2021 ; Yee Kuen and Masarudin, 2022 ).…”
Section: Discussionmentioning
confidence: 99%